Anti-de Sitter holography for gravity and higher spin theories in two dimensions - Grumiller, Daniel (2014)
We provide a holographic description of two-dimensional dilaton gravity with Anti-de Sitter boundary conditions. We find that the asymptotic symmetry algebra consists of a single copy of the Virasoro algebra with non-vanishing central charge and point out difficulties with the standard canonical treatment. We generalize our results to higher spin theories and thus provide the first examples of two-dimensional higher spin gravity with holographic description. For spin-3 gravity we find that the asymptotic symmetry algebra is a single copy of the W_3-algebra.